Survey of Thysanoptera occurring on vegetable crops as potential Tospovirus vectors in Mendoza, Argentina - Borbón, Carlos de (1999)
Tospoviruses severely affect tomato, lettuce and other crops in Argentina' and are thrips transmitted in nature. The epidemiology of tospoviruses is closely related with vector's ecology. The aim of this study was to know the Thysanoptera fauna in and around the tomato ecosystem of the Mendoza province" and to find rearingmethods for the more common species. Thrips were collected frorn 51 host plants and 19 species were identified, five of which [Bregmatothrips venustus Hood, Chirothrips frontalis Williams, C. texanus (Andre), Frankliniella frumenti Moulton, and F. valdiviana Sakimura &O'Neill] are new records for Mendoza and Karnyothrips longiceps (Hood) for Argentina. Three out of the eight species reported to transmit tospoviruses are present in Mendoza: F. schultzei (Trybom). F. occidentalis (Pergande) and Thrips tabaci Lindeman. Rearing rnethods were developed for eight species: Aptinothrips rufus (Haliday), F. australis Morganl F. frumenti, F. gemina (Bagnall), F. occidentelis, F. schultzei, Haplothrips trellesi Moulton, and T. tabaci. Colonies were reared from a single female in a growth room at 25° (± 2) and L 12: 0 12.